Jenis - Jenis Mamalia Di Koto Baru Nagari Paninggahan Kabupaten Solok Sumatera Barat - Fikriya - Rahma; Wilson - Novarino; Rizaldi - Rizaldi (Universitas Andalas, 2015)
An inventory of mammalian species from Koto Baru Paninggahan Solok West Sumatera was conducted from August to October and continued from November to December 2015. The animals were identified through photographes from camera traps, personal encounters as well as indirect observations including foot prints and interviews to local inhabitants. This study has documented 15 species of mammals which belong to 11 families and 6 orders. From a total 511 identified photograps, it was known that pig-tailed macaque (Macaca nemestrina) was the most frequently photographed (212 images) and sambar deer (Rusa unicolor) was the least frequently photographed (3 images).